Effect of Water Management under Different Soil Conditions on Cadmium and Arsenic Accumulation in Rice - Xia Li; Ya Zhou; Lihui Luo; Peng Wang; Rui You (Agronomy, 2023)
Water management and soil conditions affect the bioavailability of cadmium (Cd) and inorganic arsenic (As) in the soil, and hence, their accumulation in rice grains. A field experiment was conducted to investigate the effects of two water management regimes (flooding and dry–wet alternation) on Cd and inorganic As uptake and transport in rice under different soil conditions (paddy soil developed from gray-brown alluvium, K1; paddy soil developed from weathered shale and slate, K2) in the Sichuan Basin, Western China. The results indicated that compared to the wet–dry rotation, long-term flooding led to a substantial decrease of 49.3~55.8% in soil-available Cd content (p < 0.05), accompanied by a significant increase of 16.0~74.2% in As(Ⅲ) content (p < 0.05), causing no significant difference in As(V) content at the K1 site (p > 0.05). However, differences in soil-available Cd and inorganic As content under different water management treatments were both insignificant at the K2 site (p > 0.05). Long-term flooding treatment at the K1 site resulted in a remarkable reduction of 90.2% in Cd content in rice husks and 92.2% in brown rice (p < 0.05), along with a significant increase of 263.6% and 153.3%, respectively, in As(Ⅲ) content; no significant differences in As(V) content were observed at the K2 site (p > 0.05). In conclusion, the effect of water management on rice Cd and inorganic As varied under different soil conditions, with the change in rice Cd and inorganic As in paddy soil developed from gray-brown alluvium being significantly greater than that in paddy soil developed from weathered shale and slate.